2017
DOI: 10.1017/s2040174417000939
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisphenol A treatment during pregnancy on kidney development in mice: a stereological and histopathological study

Abstract: Bisphenol A (BPA) is a chemical found in plastics that resembles oestrogen in organisms. Developmental exposure to endocrine-disrupting chemicals, such as BPA, increases the susceptibility to type 2 diabetes (T2DM) and cardiovascular diseases. Animal studies have reported a nephron deficit in offspring exposed to maternal diabetes. The aim of this study was to investigate the prenatal BPA exposure effects on nephrogenesis in a mouse model that was predisposed to T2DM. This study quantitatively evaluated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
0
26
1
Order By: Relevance
“…Therefore, total glomerular volume (the multiple of glomerular number and mean volume) is proposed as a useful indicator of filtration surface area (Nyengaard and Bendtsen, ). It is important to note that the glomerular number and the glomerular volume have an inverse relationship within the same species (Nuñez et al, ). Physiologically, reduction in nephron number may cause glomerular hyperfiltration, which leads to increase in glomerular hydrostatic pressure and glomerular hypertrophy to maintain renal function (Puelles et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, total glomerular volume (the multiple of glomerular number and mean volume) is proposed as a useful indicator of filtration surface area (Nyengaard and Bendtsen, ). It is important to note that the glomerular number and the glomerular volume have an inverse relationship within the same species (Nuñez et al, ). Physiologically, reduction in nephron number may cause glomerular hyperfiltration, which leads to increase in glomerular hydrostatic pressure and glomerular hypertrophy to maintain renal function (Puelles et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most stereological investigations on the kidney have been carried out on laboratory animals such as mouse (Arsenault et al, ; Walton et al, ; Nuñez et al, ) and rat (Şimşek et al, ; Khoshvakhti et al, ; Melchioretto et al, ; Seravalli et al, ), and also on other mammals such as nonhuman primates (Gubhaju and Black, ; Batchelder et al, ). However, apart from investigations on the kidney in pig (Cibulskyte et al, ; Karstoft et al, ; Lødrup et al, ,b), sheep (Bains et al, ; Wintour et al, ) and horse (Bolat et al, ), the morphometric features of kidney of other domestic animals have not been thoroughly investigated using stereology.…”
mentioning
confidence: 99%
“…Previous findings have indicated that CeO 2 passes through the placenta [34]. In mice, the development of the metanephros is considered to begin at E10.5-11 and ends at 7-10 days after birth [49,50]. The kidney, like all other major organs of the body, is susceptible to exposure to a Regulated differentiation and proliferation of mesenchymal cells and urinary epidermal primordial cells cause nephrogenesis in the embryonic period [50].…”
Section: Discussionmentioning
confidence: 99%
“…The kidney, like all other major organs of the body, is susceptible to exposure to a wide range of chemicals during developmental periods. Regulated differentiation and proliferation of mesenchymal cells and urinary epidermal primordial cells cause nephrogenesis in the embryonic period [ 50 ]. Kidney development in mice is completed two weeks after birth [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we need an effective method for diagnosis of kidney cancer, which may lay the foundation for its potential treatment and cure. 5 There are already many signs of progress in the next sequencing technologies from the past years. Some reports have shown that only 10% of the genes were transcribed into coding RNAs, while 90% of the RNAs can be named as the noncoding RNAs (ncR-NAs).…”
Section: Introductionmentioning
confidence: 99%